The dynamic effect of rural-to-urban migration on inequality in source villages: System GMM estimates from rural China - Wei Ha; Junjian Yi; Ye Yuan; Junsen Zhang (China Economic Review, 2016)
Using a newly constructed panel dataset that covers the 14-year period from 1997 to 2011 for more than 100 villages in China, this study analyzes the dynamic effect of rural-to-urban migration on inequality in source villages. Given that income inequality is time persisting, we use a system GMM framework. We found that the dynamic relationship between migration and income inequality is inversely U-shaped. Specifically, contemporary migration increases income inequality, whereas lagged migration has a strong income inequality-reducing effect on the sending villages. A 50 percent increase in the lagged migration rate translates into a one-ninth to one-tenth standard deviation reduction in income inequality.